A fluorescence red-shift and turn-on sensor for acetylacetone derived from ZnII-based metal–organic framework with new topology. Issue 13 (17th March 2021) - Li, Le-Qian; Yao, Shu-Li; Tian, Xue-Mei; Zheng, Teng-Fei; Li, Jin-Yan; Liu, Sui-Jun; Chen, Jing-Lin; Yu, Mei-Hui; Wen, He-Rui
Abstract : JXUST-4 with a rare (3, 3, 7)-c topology net has been prepared, acting as a fluorescent sensor for acac through obvious fluorescence red-shift and enhancement with excellent properties. Abstract : A three-dimensional metal–organic framework, namely [Zn3 (BIBT)(BTC)5/3 (μ3 -OH)]·solvents n (JXUST-4 ), has been synthesized by using Zn II ions, and BIBT and H3 BTC ligands (BIBT = 4, 7-bi(1 H -imidazol-1-yl)benzo-[2, 1, 3]thiadiazole and H3 BTC = 1, 3, 5-benzenetricarboxylic acid). JXUST-4 shows a new (3, 3, 7)-connected topology net containing a trinuclear Zn II cluster, uncoordinated N atoms of BIBT and uncoordinated carboxylate O atoms of H3 BTC, which facilitates the interaction between the framework and analytes. Fluorescence studies indicate that JXUST-4 generates light yellow luminescence, which could be ascribed to ligand-centered emission. More importantly, JXUST-4 could be viewed as an effective fluorescent sensor toward acetylacetone through an obvious fluorescence red-shift with high sensitivity, efficient selectivity, and outstanding recycling capacity. Furthermore, the possible sensing mechanism of JXUST-4 toward acetylacetone is due to electron transfer and weak interactions between the analyte and framework.